Development of Interactive Learning Media Based on Google Sites Application for Matrix Multiplication Material - Alexander Hendro Risit; Abd Qohar (Green Publisher, 2025)
The rapid advancement of information technology has brought significant changes to the educational landscape, with web-based learning becoming an essential tool in enhancing learning outcomes. This research aims to develop interactive learning media based on the Google Sites application to support the teaching of matrix multiplication operations, a concept that often challenges high school students. The goal is to create a media tool that can improve students’ understanding and facilitate independent learning, particularly in the context of mathematics education. Using the Research and Development (R&D) method, this study follows the ADDIE model, which includes stages of Analysis, Design, Development, Implementation, and Evaluation. The learning media was developed and validated through expert feedback, with the effectiveness assessed via practicality and validation tests. A trial with 11 students from the S-2 Mathematics Education Program at the State University of Malang was conducted to gather feedback on the media’s usability and interactivity. The results showed that the Google Sites-based learning media was both valid and practical, with an average validation score of 3.5 and a practicality score of 3.8. These scores indicate that the media is suitable for educational use, engaging students in the learning process. The interactive features, including simulations and video content, supported students in better understanding matrix multiplication. This research contributes to the development of web-based learning media, offering a viable tool for enhancing mathematics education. Future studies could explore extending this media to other mathematical topics and evaluate its effectiveness across various student competencies.